The Relationship Between Diet Patterns and Dental Caries in Preschool Children: Study at Muslimah Nu Islamiyah Kindergarte, Taman Sidoarjo - Zhorif Abrial Afif; Bambang Hadi Sugito; Ida Chairanna Mahirawatie (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Dental caries is still a common problem, especially in children under 6 years old. Diet is a way of regulating the type and amount of food to maintain nutrition, prevent disease and maintain a healthy body. In August 2024, researchers conducted dental examinations on 10 children at the Muslimah NU Islamiyah Taman Sidoarjo Kindergarten and all had dental caries with an average def-t of 4.6. The aim is to determine whether there is a relationship between diet and dental caries in preschool children at Muslimah NU Islamiyah Taman Sidoarjo Kindergarten. This study used a quantitative method with a Cross Sectional research design. A total of 36 respondents were selected according to the specified criteria. he results showed that the value (p-value 0.001 <0.05). Data were collected through dental caries examination forms and dietary pattern questionnaires. Data analysis using the chi-square test. The results showed that there was a relationship between diet and dental caries in preschool children at Muslimah NU Islamiyah Kindergarten Taman Sidoarjo in 2025.